2020
DOI: 10.1177/1460458220935369
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing vessel visibility in fundus images to aid the diagnosis of retinopathy of prematurity

Abstract: Retinopathy of prematurity is a disease that can affect premature or in similar conditions babies. For diagnosing of retinopathy of prematurity, the infant is examined as soon as possible. Due to the nature of the examination, the images obtained are poor in quality. This article presents an automated method for processing fundus images to improve the visibility of the vascular network. The method includes several processing tasks whose parameters are predicted using an artificial neural network. A set of 88 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Zhou et al [44] proposed the learning of discriminative CNN features and enhanced thin vessels in color fundus images to further improve the segmentation performance. This algorithm improves the contrast of the retinal vessels and was verified by three pediatric ophthalmologists [45]. Goel et al [46] showed that using a development learning model to transfer learning can improve the accuracy of correct classification of different aneurysms in the retina area caused by DR. AI technology can improve diagnosis accuracy and can also save time for both doctors and patients by increasing the contrast between image structures, such as segmenting distinct blood arteries or calculating normal and pathological structures.…”
Section: Enhancementmentioning
confidence: 87%
“…Zhou et al [44] proposed the learning of discriminative CNN features and enhanced thin vessels in color fundus images to further improve the segmentation performance. This algorithm improves the contrast of the retinal vessels and was verified by three pediatric ophthalmologists [45]. Goel et al [46] showed that using a development learning model to transfer learning can improve the accuracy of correct classification of different aneurysms in the retina area caused by DR. AI technology can improve diagnosis accuracy and can also save time for both doctors and patients by increasing the contrast between image structures, such as segmenting distinct blood arteries or calculating normal and pathological structures.…”
Section: Enhancementmentioning
confidence: 87%
“…Zhou et al [ 44 ] proposed the learning of discriminative CNN features and enhanced thin vessels in color fundus images to further improve the segmentation performance. This algorithm improves the contrast of the retinal vessels and was verified by three pediatric ophthalmologists [ 45 ]. Goel et al [ 46 ] showed that using a development learning model to transfer learning can improve the accuracy of correct classification of different aneurysms in the retina area caused by DR.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate regions of exudates were detected using the k-means clustering technique, which provides a good result when the retinal OD is fully visible and fails if only a portion of the OD is visible. Some researchers confirm the need for pre-processing to improve the image quality [13,14]. Pazmino et al [13] presented a method for processing fundus images to improve the visibility of the vascular network.…”
Section: Related Research Workmentioning
confidence: 99%
“…Some researchers confirm the need for pre-processing to improve the image quality [13,14]. Pazmino et al [13] presented a method for processing fundus images to improve the visibility of the vascular network. Luangruangrong [14] used contrast limited adaptive histogram equalization (CLAHE) for image enhancement, then optic disk and blood vessel detection followed by classifying exudates using hierarchical fuzzy-c-mean clustering.…”
Section: Related Research Workmentioning
confidence: 99%